PENGARUH PERCEIVED ENJOYMENT, PERCEIVED USEFULNES, PERCEIVED EASE OF USE, PERCEIVED COMPABILITY, PERCEIVED INFORMATION SECURITY, DAN PERCEIVED SOSIAL PRESSURE TERHADAP SIKAP TERHADAP BELANJA ONLINE - Cen Lu,; Abednego, Felicia; Kuswoyo, Chandra; Calvin, Laurentius (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Changes in consumer behavior in shopping from buying in stores to buying online make companies need to create e-commerce systems that are more attractive to customers. Companies in this case need to know how online consumer shopping styles (internet shopper lifestyle) relate to their attitudes towards online shopping. Online shopping already exists in Indonesia, but consumers are not used to shopping online. However, this reality changed after the development of e-commerce where many consumers shop online from various online sites. The aim of this research is to look at the internet shopper lifestyle towards attitude toward online shopping. Internet shopper lifestyle is seen from several dimensions such as perceived enjoyment, perceived usefulness, perceived ease of use, compatibility, perceived information security and perceived social pressure. Researchers will examine a sample of people from Greater Bandung through an online questionnaire regarding their attitudes towards online shopping. The results showed that perceived information security and perceived enjoyment had no effect on attitude toward advertising, while perceived ease of use, perceived compatibility, perceived social pressure, and perceived usefulness had an effect on attitude toward advertising. Keywords : perceived enjoyment, perceived usefulness, perceived ease of use, compatibility, perceived information security, perceived social pressure